2016
DOI: 10.1016/j.ajpath.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in Nucleoporin 35 Causes Murine Degenerative Colonic Smooth Muscle Myopathy

Abstract: Chronic intestinal pseudo-obstruction (CIPO) is a rare but life-threatening disease characterized by severe intestinal dysmotility. Histopathologic studies in CIPO patients have identified several different mechanisms that appear to be involved in the dysmotility, including defects in neurons, smooth muscle, or interstitial cells of Cajal. Currently there are few mouse models of the various forms of CIPO. We generated a mouse with a point mutation in the RNA recognition motif of the Nup35 gene, which encodes a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Two such candidate genes involved in muscle differentiation include BIN1 and NUP35 . Variants within BIN1 and NUP35 on OAR2 have been previously associated with muscle myopathy in humans and mice, although their role in sheep is unknown [ 66 , 67 ]. However, it most likely that the nucleoporin NUP35 plays an important role in myogenic differentiation through the formation of the nuclear pore complex [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two such candidate genes involved in muscle differentiation include BIN1 and NUP35 . Variants within BIN1 and NUP35 on OAR2 have been previously associated with muscle myopathy in humans and mice, although their role in sheep is unknown [ 66 , 67 ]. However, it most likely that the nucleoporin NUP35 plays an important role in myogenic differentiation through the formation of the nuclear pore complex [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed no difference in the distribution of goblet cells in the gut epithelium from both groups of quail. The increase in the thickness of the muscularis externa observed in the colon from HS quail suggests the presence of smooth muscle hypertrophy, a condition that generally occurs when there is a functional impairment of the organ due to hormonal changes [ 105 ] and/or intestinal obstruction [ 106 , 107 ]. The function of the colonic muscularis in terms of smooth muscle contractility or colonic peristalsis in quail divergent for corticosterone responses to stress has not been yet investigated; however, it will be an interesting aspect to address in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Their amplitude is consistently smaller of two order of magnitudes than endogenous pulsatile ones, because the 1kPa stress is here magnetically produced directly in the conjunctive epithelial tissue that includes epithelial crypts only. Indeed, the latter is ten times thinner than the visceral smooth muscle from which the 1kPa stress produces the endogenous peristatic movements imposed to the conjonctive and crypt tissues 35 (see Supplementary Note 3d ). Thus, the magnetic treatment does not rescue the physiological amplitude and propagative nature of the overall colonic structure pulsatile movements, but rescues in the conjonctive and epithelial cells of interest the physiological pulsatile 1 kPa high-frequency stress pressure of 2 s generated by associated physiological movements.…”
Section: Resultsmentioning
confidence: 99%